Reinforcing public responsibility?: influences and practices in street-level bureaucrats' engagement in policy design - Lavee, Einat; Cohen, Nissim and Nouman, Hani (2018)
Previous literature demonstrates that when street?level bureaucrats believe that the policy as designed is not desirable, they utilize various strategies to change the situation. This study suggests that when street?level bureaucrats believe that fixing a policy through the manner in which it is implemented is not enough, they will try to influence the design of the policy directly. Three factors promote this decision: public perceptions revealed in their interactions with clients, professional ethical values and a supportive organizational environment. We test this argument using Israeli public social workers in the context of urban renewal. We discuss the problems and benefits of involving street?level bureaucrats in policy design and view such actions as related to welfare reform and changes in the state's responsibility for its citizens. We maintain that in this changing environment, street?level bureaucrats' involvement in policy design should be formally institutionalized. - Reproduced.
Keywords: Bureaucracy; Policy design